2016
DOI: 10.1111/pce.12794
|View full text |Cite
|
Sign up to set email alerts
|

OsPAP10c, a novel secreted acid phosphatase in rice, plays an important role in the utilization of external organic phosphorus

Abstract: Under phosphate (Pi ) starvation, plants increase the secretion of purple acid phosphatases (PAPs) into the rhizosphere to scavenge organic phosphorus (P) for plant use. To date, only a few members of the PAP family have been characterized in crops. In this study, we identified a novel secreted PAP in rice, OsPAP10c, and investigated its role in the utilization of external organic P. OsPAP10c belongs to a monocotyledon-specific subclass of Ia group PAPs and is specifically expressed in the epidermis/exodermis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
85
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 33 publications
(103 reference statements)
2
85
0
1
Order By: Relevance
“…In rice, several APase isoforms corresponding to OsPAP10c, rice novel secreted purple APase, were identified using in-gel activity assays [33]. OsPAP10c overexpression increased the accumulation of four APase isoforms in transgenic rice plants; in addition, the results suggested that OsPAP10c could form different homo-or heteromeric protein complexes [33].…”
Section: Modification Of Acid Phosphatase Activity and Localization Amentioning
confidence: 99%
See 4 more Smart Citations
“…In rice, several APase isoforms corresponding to OsPAP10c, rice novel secreted purple APase, were identified using in-gel activity assays [33]. OsPAP10c overexpression increased the accumulation of four APase isoforms in transgenic rice plants; in addition, the results suggested that OsPAP10c could form different homo-or heteromeric protein complexes [33].…”
Section: Modification Of Acid Phosphatase Activity and Localization Amentioning
confidence: 99%
“…Activity of AtPAP10, a major Pi starvation-induced APase associated with the root surface in Arabidopsis is probably regulated both through local and systemic signaling under Pi starvation [24]. In a recent study, Lu et al [33] identified a novel secreted purple APase in rice (OsPAP10c) and investigated its role in organic P utilization -OsPAP10c overexpression significantly increased APase activity both in leaves and roots, but especially on the root surface and in culture media. Studies by Wang et al [47] indicated that the quantity of rhizosphere APase had positive correlations with P fractions available to plants and Pi uptake by the plants in low-Pi soils; these authors also stated that both Brassica napus and Avena sativa were good candidates to study P utilization.…”
Section: Modification Of Acid Phosphatase Activity and Localization Amentioning
confidence: 99%
See 3 more Smart Citations